Impaired KIN10 function restores developmental defects in the Arabidopsis trehalose 6‐phosphate synthase1 (tps1) mutant. Issue 1 (8th April 2022) - Zacharaki, Vasiliki; Ponnu, Jathish; Crepin, Nathalie; Langenecker, Tobias; Hagmann, Jörg; Skorzinski, Noemi; Musialak‐Lange, Magdalena; Wahl, Vanessa; Rolland, Filip; Schmid, Markus
Summary: Sensing carbohydrate availability is essential for plants to coordinate their growth and development. In Arabidopsis thaliana, TREHALOSE 6‐PHOSPHATE SYNTHASE 1 (TPS1) and its product, trehalose 6‐phosphate (T6P), are important for the metabolic control of development. tps1 mutants are embryo‐lethal and unable to flower when embryogenesis is rescued. T6P regulates development in part through inhibition of SUCROSE NON‐FERMENTING1 RELATED KINASE1 (SnRK1). Here, we explored the role of SnRK1 in T6P‐mediated plant growth and development using a combination of a mutant suppressor screen and genetic, cellular and transcriptomic approaches. We report nonsynonymous amino acid substitutions in the catalytic KIN10 and regulatory SNF4 subunits of SnRK1 that can restore both embryogenesis and flowering of tps1 mutant plants. The identified SNF4 point mutations disrupt the interaction with the catalytic subunit KIN10. Contrary to the common view that the two A. thaliana SnRK1 catalytic subunits act redundantly, we found that loss‐of‐function mutations in KIN11 are unable to restore embryogenesis and flowering, highlighting the important role of KIN10 in T6P signalling.